Medical students’ attitudes concerning medical ethics courses in AL-Kindy medical college 2013-2014 - Lafta, Haitham H.; Hussein, Wijdan A.; Ismaeel, Salah. A; Ibrahim, Mohammed A. (AL-Kindy College Medical Journal, 2014)
ABSTRACTBackground: In Medical ethics education, improving medical student’s attitudes toward respecting the right of patients is an essential task. The medical students’ attitude has been affected by social, educational and personality background factors.Objective: To investigate medical student’s attitudes regarding medical ethics courses.Method: The study was conducted in Al-Kindy College of Medicine on academic year (2013 -2014) for the period from January to September. A cross- sectional study design was adopted with a self- administered questionnaire form distributed to medical students in the 5th-6th under graduate grades. The questionnaire consisted of 31 items relevant to student’s opinion about attitudes concerning ethics courses.Result: Out of overall 113 students 90(78.1%) responded, the majority 88.9% considered medical ethics teaching for medical students an important issue, and 85.5% had general interest in learning more about medical ethics. However, about 84.4% agreed that medical ethics teaching would influence the attitudes and behaviors of doctors, and improvepatient doctor relationship, but about 65.6% of students were confident with their ability to recognize significant ethical problems in clinical practice. Only 46.7% knew how to proceed when a patient is mentally incompetent.Conclusion: Medical students have positive knowledge andattitude about the medical ethics teaching, but they may notbe adequately prepared to meet the challenges of clinicalpractice. There should be incorporation of creative andintegrated ethics curriculum to start in the first medical grade,with emphasis on ethical aspect of daily medical practice.